Rechtliche Voraussetzungen der Nutzung von Open-Source-Software in der öffentlichen Verwaltung, insbesondere des Kantons Bern - Poledna, Tomas (Carl Grossmann Verlag, 2017)
The work has been authored by 3 experts in enforcement law to analyse whether an administration or government may release software as open source.